Awareness, Knowledge, and Practice on Retinal Diseases at High-altitude of Nepal - Thapa, Raba; Ruit, Sanduk; Neupane, Pratibha; Poudel, Manish; Banjara, Pradeep; Duwal, Sushma; Gurung, Elena; Tabin, Geoffrey Craig (Nepalese Journal of Ophthalmology, 2026)
Introduction: Retinal disorders are the major causes of visual impairment in Nepal. Limited access to eye care service in high altitude regions, along with low awareness and knowledge on the retinal diseases delays timely treatment and care. Objective: To assess the awareness, knowledge, and practices on major retinal disorders at high-altitude in Nepal. Methodology: An analytical cross-sectional study was carried out to assess the retinal disease prevalence at three high-altitude districts of Nepal namely Manang, Mustang, and Solukhumbu from 2023 May to 2023 July after ethical clearance. The sample size of 308 with the age 40 years and above were included with random sampling. Awareness, knowledge, and practice on major retinal disease on diabetic retinopathy (DR), age-related macular degeneration (AMD), hypertensive retinopathy (HR), and high-altitude retinopathy (HAR) were assessed. Facetoface interviews were conducted after obtaining informed written consent. Ethical approval was granted by the Nepal Health Research Council, and data were analysed using IBM SPSS v.20. Result: A total of 338 study participants were enrolled. The mean age was 56.98±11.13 years with female preponderance (216, 63.9%). Three-fifth (61.8%) were literate. Awareness was found among 131 (38.76%) on diabetes mellitus affecting eye, 19 (5.6%) on AMD, 118 (34.9%) on hypertension affecting eye, and 273 (80.8%) on high-altitude affecting eye. However, only five (1.5%) were aware that high-altitude could affect retina and none were aware of its preventive measures. Eleven (33.3%) of people with diabetes had regular eye exams. One respondent had AMD, however he did not receive frequent eye examinations. Only eight (8.3%) of those with hypertension had undergone regular eye check-ups. Conclusion: The awareness, knowledge, and practice on major retinal diseases including high-altitude retinopathy was low among the population of high-altitude in Nepal. Emphasis should be given on raising awareness activities besides enhancing the access to eye care services.